Measuring social capital : an integrated questionnaire - Grootaert, Christiaan; Narayan, Deepa; Jones, Veronica Nyhan; Woolcock, Michael (Washington, D.C. : World Bank, 2004)
The publication is part of the World Bank Working Paper Series. It is published to communicate the result of the Bank's ongoing research and to stimulate public discussion.
Includes bibliographical references (p. 51-53).
gp. 25/01/2019
Loan
Keywords: Social capital (Sociology); Questionnaires